Isolated tubercular hypoglossal nerve paralysis. (July 2017) - Thakur, JS; Verma, Naina; Mohindroo, Shobha; Azad, Ramesh K; Mohindroo, NK
Hypoglossal nerve palsy is not an uncommon neurological finding but primary nasopharyngeal tuberculosis (TB) presenting as hypoglossal nerve palsy is very rare. A 31-year-old woman presented with headache and progressive tongue deviation towards the right side. Diagnostic nasal endoscopy revealed soft tissue mass lesion on the posterior wall of nasopharynx while MRI revealed isointense tumour in nasopharynx with normal hypoglossal nerve and brain. Histopathological examination found TB. We discuss the clinical challenges and possible pathogenesis of this rare clinical entity.